Neuromodulación tibial posterior transcutánea en el tratamiento de la incontinencia fecal - Manríquez G., Valentín; Sandoval S., César; Blümel M., Bernardita (Revista Hospital Clínico Universidad de Chile, 2010)
Fecal incontinence is a pathological condition that severely affects quality of life. Few therapeutic tools are available for treating this condition, some of them with variable success. Transcutaneous electrical nerve stimulation (TENS) has become a new treatment option in the last years. In this article we review TENS technique, mechanism of action, and the available evidence in medical literature of its effectiveness.